Tiden ødelægger alt. Om episodisk bagvendte fortællinger illustreret ved hjælp af Gaspar Noés Irréversible - Hansen, Per Krogh (K&K - Kultur og Klasse, 2011)
TIME DESTROYS EVERYTHING | This article focuses on what Seymour Chatman calls ‘sustained episodic reversal’ of narrative progressionR– that is, narratives in which the sequential, chronological order of the events is reversed and thereby ‘de-’ or ‘unnaturalized’. The article opens with a short discussion of the project of ‘unnatural narratology,’ and it is claimed that if our experience of a given narrative as ‘natural’ is grounded on its confirmation of the conventions for the mode or genre the narrative belongs to, then the task for an ‘unnatural narratology’ is to investigate the exceptions, that is, cases where conventions are broken and perhaps reformulated. Sustained episodic reversals of event sequences belong to this field of interest insofar as one of the basic features of ‘natural narrative’ is that the sequence of clauses (or more generally, the sjuzhet or discourse) is typically matched to the sequence of the events being narrated (the fabula or story). The denaturalizing function and effect of the sustained reversal is illustrated through analysis of Gaspar Noé’s Irréversible (2002). It is shown that the reversal has radical consequences for the spectator’s (re)construction of the narrative’s fabula, and that it engages the reader in a game of post hoc ergo propter hoc and of narrative construction and deconstruction.